2011
DOI: 10.1128/cvi.00032-11
|View full text |Cite
|
Sign up to set email alerts
|

OdDHL Inhibits T Cell Subset Differentiation and Delays Diabetes Onset in NOD Mice

Abstract: Some infectious diseases have been shown to halt the onset of autoimmune disease in animal models and have been suggested to also influence autoimmune pathology in humans. The isolation and study of small molecules and proteins from the infectious agents responsible for the protective effect will enable a mechanistic understanding of how these components may prevent or delay the onset of autoimmunity. In this study we confirm that the quorum-sensing signal molecule OdDHL from Pseudomonas aeruginosa can delay t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Small molecules/proteins isolated from the infectious agents have shown to account for these protective effects [94]. Previous studies indicated that P. aeruginosa QS signal OdDHL (viz.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecules/proteins isolated from the infectious agents have shown to account for these protective effects [94]. Previous studies indicated that P. aeruginosa QS signal OdDHL (viz.…”
Section: Reviewmentioning
confidence: 99%
“…3O-C 12 - HSL) could delay the onset of type 1 diabetes (T1D) in the non-obese diabetic (NOD) mouse model. Furthermore, using an antigen-presenting cell-free system, the authors showed that 3O-C 12 -HSL could not only inhibit the proliferation of naïve T cells but directly suppress the differentiation of T cell subsets; however, no effects was seen with 3O-C 12 -HSL on the inhibition of primed and committed differentiated T cell responses, suggesting that 3O-C 12 -HSL-mediated immune mechanism may be restricted to initial stages of infection [94]. …”
Section: Reviewmentioning
confidence: 99%
“…We observed a significant decrease of diabetes incidence after IRT5 administration for 36 weeks, which was associated with reduced gut permeability and increased proportion of CCR9 + gut-tropic Treg cells. In this investigation, we started IRT5 administration at 4 weeks of age because previous studies showed that inhibition of physiological β-cell apoptosis at day 14–42 with benzyloxylcarbonyl-V-A- d - O -methyl fluoromethyl ketone (zVAD-fmk), a pan-caspase inhibitor, was able to inhibit sensitization to diabetogenic T cells ( 38 ) and immune intervention at 4 weeks of age could block the development of diabetes in NOD mice ( 39 41 ). We continued IRT5 treatment up to 40 weeks of age because diabetes developed even after 32–36 weeks of age in our NOD colonies ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…N-(3-oxododecanoyl)-l-HSL(3-oxo-C12-HSL/OdDHL). 3-oxo-C12-HSL, a specific type of acyl homoserine lactone (AHL), is an auto-inducing, quorum-sensing associated virulence factor that regulates swarming, toxin and protease production, and proper biofilm formation [ 115 , 116 ]. OdDHL inhibits naive T-Cell proliferation as well as subtype differentiation.…”
Section: Description Of Targetsmentioning
confidence: 99%
“…It also decreases antibody production at high concentrations and promotes IgE/IL-4 at low concentrations. OdDHL also regulates Las gene expression, most notably LasR, and upregulates IL-8 in corneal infections [ 115 , 116 ]. Additionally, it has been shown to inhibit dendritic cell concentrations in a dose-dependent fashion.…”
Section: Description Of Targetsmentioning
confidence: 99%